2022
DOI: 10.1287/orsc.2021.1491
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Disruptions and the Philanthropy of Multinational Firms

Abstract: This paper studies philanthropy by multinational enterprises (MNEs) during institutional disruptions—the sudden and unexpected, temporary, and systemic breakdowns in market-oriented institutions. The central argument is that, under institutional disruptions, MNEs aim to restore factors that are essential for the market to function, such as infrastructure and labor markets, and the strength of the market restoration motive is positively associated with the economic importance of the affected country to the MNE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 107 publications
0
17
0
Order By: Relevance
“…Terrorist attacks can cause significant damage, but on the other hand, the impact of a single event does not tend to last long nor be large enough to fundamentally alter the operating environment of a country (Witte, Burger, Ianchovichina, & Pennings, 2017). Thus, terrorist attacks represent episodic, nonpersistent, yet highly unpredictable disruptions to the operating environment (Ballesteros & Magelssen, 2021) and, as such, pose unique challenges to MNEs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Terrorist attacks can cause significant damage, but on the other hand, the impact of a single event does not tend to last long nor be large enough to fundamentally alter the operating environment of a country (Witte, Burger, Ianchovichina, & Pennings, 2017). Thus, terrorist attacks represent episodic, nonpersistent, yet highly unpredictable disruptions to the operating environment (Ballesteros & Magelssen, 2021) and, as such, pose unique challenges to MNEs.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the fact that a subsidiary's survival in a host country may be jeopardized by terrorist attacks does not necessarily warrant divestment as a reasonable response. In fact, given the temporary and nonpersistent nature of terrorism (Ballesteros & Magelssen, 2021), divestment is an overly costly response and may seldom be economically rational. For example, recent research on temporary environmental disruptions has shown that, although such disruptions can negatively affect MNE subsidiaries’ operations and survival, a more economically rational decision is for MNEs to keep committed to the event host country and help restore the environment (Ballesteros & Magelssen, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Global Times (2020) reported that 14 million items of medical supplies, such as face masks, testing kits, and thermometers, have been donated worldwide from Chinese firms such as Alibaba or Fosun. In addition, tech companies with substantial operations in China, such as Apple, donated millions of dollars in medical resources in the initial stages of the coronavirus outbreak to protect their workforce (Ballesteros and Magelssen, 2021). On the other hand, some companies have chosen to pursue short-term gains by reducing or abandoning their social commitments.…”
Section: Introductionmentioning
confidence: 99%
“…The drivers of philanthropic activities in stable institutional settings can be different from those in disrupted conditions, as firms will be fighting for their survival by pulling together with governments and non-investing stakeholders for the restoration of economic institutions (Ballesteros and Magelssen, 2021). The extant literature suggests that firms operating in disaster areas contribute more toward disaster relief efforts (Muller and Whiteman, 2009).…”
Section: Introductionmentioning
confidence: 99%